2016
DOI: 10.1038/ncomms10590
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic partner selection during retinal circuit reassembly varies with timing of neuronal regeneration in vivo

Abstract: Whether neurons can restore their original connectivity patterns during circuit repair is unclear. Taking advantage of the regenerative capacity of zebrafish retina, we show here the remarkable specificity by which surviving neurons reassemble their connectivity upon regeneration of their major input. H3 horizontal cells (HCs) normally avoid red and green cones, and prefer ultraviolet over blue cones. Upon ablation of the major (ultraviolet) input, H3 HCs do not immediately increase connectivity with other con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 50 publications
(62 reference statements)
6
83
0
Order By: Relevance
“…Our current study shows that replacement neurons are able to form synapses with mature circuitry, an observation previously made in other CNS systems after damage [2426, 30, 32, 33, 4044]. Further, we found that although regenerated xfz43 BCs establish their original numbers of input synapses, the axons of all three BC types doubled their number of ribbons.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our current study shows that replacement neurons are able to form synapses with mature circuitry, an observation previously made in other CNS systems after damage [2426, 30, 32, 33, 4044]. Further, we found that although regenerated xfz43 BCs establish their original numbers of input synapses, the axons of all three BC types doubled their number of ribbons.…”
Section: Discussionsupporting
confidence: 87%
“…To visualize individual BCs, we injected pUAS:MYFP or pUAS:MmTFP1myc [44] into single-cell stage embryos from the xfz43 line. To track the same retinal areas across ages for live-imaging, we injected pCrx:MYFP [39] into single-cell embryos from xfz43 fish crossed with the Vsx1 line (see Supplemental Experimental Procedures).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work suggests that the formation of functional synapses after input loss is possible. For example, recent work in the zebrafish retina suggests that, after postsynaptic neurons are killed, newly born neurons can form synapses with the presynaptic partners but only during a limited time window (Yoshimatsu et al 2016). More systems to study dendrite regeneration will be required to address whether dendrites regenerated by injured, but not killed, neurons can form functional synapses.…”
Section: Comparison With Other Studies Of Dendrite Regenerationmentioning
confidence: 99%
“…Proliferative cells show a bias towards generating ablated cell fates, but also generate non-ablated cells [33, 35, 36]. This shows their intrinsic multipotency and may reflect recapitulation of intrinsic molecular processes that control temporal cell fate decision as observed in development.…”
Section: Introductionmentioning
confidence: 99%